Silver-loaded glass antibacterial agent, preparation method thereof and product
Patent Information
- Application Number
- CN202510704738.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of antibacterial materials technology, specifically relating to a silver-loaded glass antibacterial agent, its preparation method, and the product thereof. Background Technology
[0002] Existing silver-impregnated glass antibacterial agents typically involve adding Ag₂O directly during glass preparation and then grinding it into powder of the desired particle size. However, this method results in the same Ag₂O content on the surface and inside the glass particles, meaning the surface Ag₂O is the primary active agent. Furthermore, the high cost of Ag₂O limits its addition to resins and other materials, requiring a minimum dosage. Additionally, experimental studies have shown that adding silver-containing glass powder to resins accelerates aging and yellowing of the plastic over time, affecting both material performance and aesthetics.
[0003] Patent application CN2024110821056 discloses a silver-impregnated antibacterial agent for high-transparency AS resin. This invention relates to the field of antibacterial materials and provides a silver-impregnated antibacterial agent for high-transparency AS resin. The silver-impregnated antibacterial agent, by weight percentage of oxides, comprises the following components: 50-60 wt% B2O3, 3-10 wt% P2O5, 0.1-3 wt% SiO2, 5-10 wt% Al2O3, 25-35 wt% MgO, 0.8-2 wt% Ag2O, 0.001-0.03 wt% CuO, and 0.003-0.05 wt% Co2O3. The glass is formed using a blown glass process. The high-transparency antibacterial AS resin material prepared using the silver-impregnated antibacterial agent of this invention exhibits a haze increase of less than 5% and a light transmittance decrease of less than 3% for a 3 mm thick sample. Summary of the Invention
[0004] To overcome the following shortcomings in existing technologies: 1. The Ag2O content on the surface and inside of the glass microparticles manufactured in existing technologies is the same, resulting in high usage costs; 2. When Ag2O-containing glass powder is added to resin, it gradually accelerates the aging and yellowing of the plastic over time. This solution introduces specific amounts of alumina and alkali metal ions, sodium oxide and potassium oxide, to prepare Ag2O-free matrix glass. After grinding the powder to the required particle size, ion exchange is performed. The first ion exchange introduces a high surface content of Ag2O, and preferably includes a second ion exchange to appropriately increase the alkali metal K2O content of the high surface Ag2O content, thereby maintaining a high surface Ag2O content while inhibiting the aging and yellowing of the resin caused by Ag2O. This achieves lower cost preparation of Ag2O-containing antibacterial glass, and when added to resin, a lower amount is required to achieve the same antibacterial effect, with less impact on the aging and yellowing of the resin. The specific technical solution of this invention is as follows: The first technical solution provided by this invention is: a silver-loaded glass antibacterial agent, wherein the silver oxide content of the silver-loaded glass antibacterial agent accounts for 5-8 wt% of the silver-loaded glass antibacterial agent with a surface thickness of 0-50 nm, and accounts for [r]% of the total glass antibacterial agent. 3 -(r-0.05) 3 ] / r 3 ×W, where r is the radius of the silver-loaded glass antibacterial agent, and W is the mass percentage of silver oxide content in the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm. The silver-loaded glass antibacterial agent is in powder form with an average particle size of 4-6µm. Taking a glass antibacterial agent with a particle size of 4µm and a radius of 2µm as an example, when the silver oxide content in the glass antibacterial agent with a surface thickness of 0-50nm is 5wt%, its mass percentage in the total mass is = (2 × W). 3 -1.95 3 ) / 2 3 ×5wt%=0.366wt%; When the silver oxide content in the antibacterial agent of glass with a surface thickness of 0-50nm is 6wt%, it accounts for the total mass fraction = (2 3 -1.95 3 ) / 2 3 ×6wt%=0.439wt%; When the silver oxide content in the antibacterial agent of 0-50nm thick glass is 7.5wt%, it accounts for (2)% of the total mass fraction. 3 -1.95 3 ) / 2 3 ×7.5wt%=0.549wt%.
[0005] Furthermore, the silver-loaded glass antibacterial agent exhibits an inhibition rate of over 99.99% against Staphylococcus aureus and Escherichia coli. Specifically, its antibacterial activity against Staphylococcus aureus is 99.99%, and its antibacterial activity against Escherichia coli is 99.9999%.
[0006] Furthermore, the raw material composition of the silver-loaded glass antibacterial agent is as follows: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2 and 0.2-0.5 wt% CeO2.
[0007] This solution also provides a method for preparing the silver-loaded glass antibacterial agent, as follows: Step 1: After preparing the raw materials, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃; Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours.
[0008] Furthermore, the raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
[0009] Furthermore, the nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is not less than 18 wt%. The proportion of silver nitrate in the total nitrate can be 18 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 98 wt%, 99 wt%, or any range or subrange between any two values.
[0010] Preferably, the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:(0.6-1), and the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1, or any range or subrange between two values.
[0011] The second technical solution provided by this invention is: a silver-loaded glass antibacterial agent, wherein silver oxide accounts for 5-8 wt% of the surface thickness of the glass antibacterial agent (0-50 nm) and [r]% of the total silver-loaded glass antibacterial agent. 3 -(r-0.05) 3 ] / r 3 ×W, where r is the radius of the silver-loaded glass antibacterial agent, and W is the mass percentage of silver oxide in the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm; at the same time, the surface of the silver-loaded glass antibacterial agent also contains 1-2wt% K2O, which accounts for 1-2wt% of the surface thickness of the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm.
[0012] Furthermore, the silver-loaded glass antibacterial agent exhibits an inhibition rate of over 99.99% against Staphylococcus aureus and Escherichia coli. Specifically, its antibacterial activity against Staphylococcus aureus is 99.99%, and its antibacterial activity against Escherichia coli is 99.9999%.
[0013] Furthermore, the raw material composition of the silver-loaded glass antibacterial agent is as follows: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2 and 0.2-0.5 wt% CeO2.
[0014] This solution also provides a method for preparing the silver-loaded glass antibacterial agent, as follows: Step 1: After preparing the raw materials, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃; Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours. The mass ratio of glass powder to nitrate can be 1:5, 1:10, 1:15, 1:20 or any range or subrange between two ratios.
[0015] Step 5: Wash the glass powder obtained in step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:(2-5). The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the finished product can be obtained.
[0016] Furthermore, the raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
[0017] Furthermore, the nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for no less than 18 wt% of the total nitrate; the second nitrate in step 5 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for 0.15-0.35 wt% of the total nitrate, and potassium nitrate accounts for no less than 70 wt% of the total second nitrate. The proportion of potassium nitrate in the total second nitrate can be 80 wt%, 82 wt%, 84 wt%, 86 wt%, 88 wt%, 90 wt%, 92 wt%, 94 wt%, 96 wt%, 98 wt%, or any range or subrange between two values.
[0018] Preferably, the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:(0.6-1), and the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1, or any range or subrange between two values.
[0019] The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:(5-7), which can be 1:5, 1:6, or 1:7, or any range or subrange between two values.
[0020] Taking the control of silver oxide content to about 5 wt% of the surface thickness of a glass antibacterial agent with a surface thickness of 0-50 nm as an example, the molecular weight of silver oxide is 232 and the molecular weight of sodium oxide is 62. To achieve the above surface content, if 1.4 wt% of the 11 wt% sodium oxide in the glass antibacterial agent powder is exchanged for silver oxide, then the original 1.4 wt% sodium oxide becomes 1.4 / 62×142=5.23 wt% silver oxide.
[0021] Phosphate glass has the following advantages: 1. Low melting point: Phosphate glass has a low melting point, making it easy to process and shape. 2. High light transmittance: It has good light transmittance in the ultraviolet to infrared band, making it suitable for optical applications. 3. Chemical stability: It is resistant to water and chemical corrosion, making it suitable for harsh environments.
[0022] 4. Low coefficient of thermal expansion: Good thermal stability, suitable for environments with large temperature variations. 5. High mechanical strength, high hardness, and good wear resistance, suitable for high-strength applications. These advantages make it widely used in optics, biomedicine, electronics, and other fields. In this invention, the main components of the phosphate glass network structure are designed with a P2O5 content of 50–55 wt%, a B2O3 content of 3–10 wt%, a SiO2 content of 2–3 wt%, and an Al2O3 content of 1–10 wt%.
[0023] It is generally believed that the addition of alkali metal oxides affects the glass melting process, particularly the reduction behavior of silver ions. Alkali metal oxides typically increase the alkalinity of glass and decrease its redox potential. This environment makes it easier for silver ions to be reduced to elemental silver. Elemental silver particles in glass can cause discoloration, usually appearing yellow or brown, especially during high-temperature firing or under extreme conditions, where the risk of discoloration is greater. The addition of alkali metal oxides also reduces the chemical resistance of glass, particularly its water resistance. Alkali metal ions are less bonded to oxygen atoms in the glass network, making them more susceptible to corrosion by water or other polar solvents. This reduced water resistance leads to silver ions dissolving more easily from the glass, increasing the risk of discoloration and decreased antibacterial properties, especially in humid or extreme environments.
[0024] This invention first prepares a glass matrix containing alkali metals, then uses a first ion exchange to allow silver ions to exchange with sodium ions on the glass surface, and then uses a second ion exchange to exchange potassium ions, which have a larger ionic radius, with silver or sodium ions. This allows silver ions to be embedded in a stable position in the glass network, thereby reducing the rate at which high concentrations of silver ions on the surface are reduced to elemental silver under prolonged light exposure, and further reducing the risk of oxidation and discoloration in the later stages.
[0025] The third technical solution provided by this invention is: a silver-loaded glass antibacterial agent product, which is composed of resin and the silver-loaded glass antibacterial agent described in the first and second technical solutions of this invention, wherein the silver-loaded glass antibacterial agent accounts for 0.15-1 wt% of the product. Further, the proportion of the glass antibacterial agent in the product can be 0.15 wt%, 0.3 wt%, 0.5 wt%, 0.75 wt%, 1 wt%, or any range or subrange between two values.
[0026] Furthermore, the resin is polystyrene (PS), styrene-acrylonitrile copolymer (AS), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate (PC), or polyethylene (PE).
[0027] Furthermore, resin products with the silver-impregnated antibacterial agent from the second scheme exhibit better anti-yellowing effects. Continuous ultraviolet irradiation (wavelength 300-700nm, 255W / m²) was performed using an ultraviolet irradiation device (CME-SEB500 equipment manufactured by Zhongwei Keneng (Beijing) Technology Co., Ltd.). 2 No yellowing occurred after 250 hours.
[0028] This invention introduces specific amounts of alumina and alkali metal ions, sodium oxide and potassium oxide, to prepare Ag₂O-free matrix glass. After grinding the matrix glass into powder of the desired particle size, ion exchange is performed, either once or twice. The first ion exchange introduces a high surface content of Ag₂O, and preferably includes a second ion exchange to appropriately increase the alkali metal K₂O content of the high Ag₂O content on the surface. This maintains a high surface Ag₂O content while inhibiting the aging and yellowing of the resin caused by Ag₂O. This achieves lower cost in preparing Ag₂O-containing antibacterial glass, and when added to resin, a lower amount is required to achieve the same antibacterial effect, with less impact on the aging and yellowing of the resin. Attached Figure Description
[0029] Figure 1 This is an SEM image of the product obtained in Example 2 of the present invention; Figure 2 A photograph of a resin article made from the product obtained in Example 2 of the present invention after 250 hours; Figure 3 SEM images of the product were obtained for Comparative Example 1; Figure 4 A photograph of a resin article made from the product of Comparative Example 1 after 150 hours. Figure 5 The image shows the test results of silver oxide, sodium oxide, and potassium oxide on the surface of the product before ion exchange in Example 2. Figure 6 The graph shows the test results of silver oxide, sodium oxide, and potassium oxide on the surface of the product in Example 2 after two ion exchanges. Detailed Implementation
[0030] The preferred embodiments of the present invention are described in detail below.
[0031] This article describes silver-loaded glass antibacterial agents, their preparation methods, and products. It includes two types of silver-loaded glass antibacterial agents, their preparation methods, and products. One type is a silver-loaded glass antibacterial agent in which silver oxide accounts for 5-8 wt% of the surface thickness of the 0-50 nm glass antibacterial agent and [r]% of the total silver-loaded glass antibacterial agent. 3 -(r-0.05) 3 ] / r 3 ×W, where r is the radius of the silver-loaded glass antibacterial agent, and W is the mass percentage of silver oxide content in the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm.
[0032] Furthermore, the silver-loaded glass antibacterial agent exhibits an inhibition rate of over 99.99% against Staphylococcus aureus and Escherichia coli.
[0033] The preparation method of this silver-loaded glass antibacterial agent is as follows: Step 1: After preparing the raw materials, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃; Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours.
[0034] Furthermore, the raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
[0035] Furthermore, the nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is not less than 18 wt%. The proportion of silver nitrate in the total nitrate can be 18 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 98 wt%, 99 wt%, or any range or subrange between two values. Preferably, the molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:(0.6-1).
[0036] The second type of silver-loaded glass antibacterial agent contains silver oxide accounting for 5-8 wt% of the surface thickness of the glass antibacterial agent (0-50 nm) and [r]% of the total silver-loaded glass antibacterial agent. 3 -(r-0.05) 3 ] / r 3 ×W, where r is the radius of the silver-loaded glass antibacterial agent, and W is the mass percentage of silver oxide in the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm; at the same time, the surface of the silver-loaded glass antibacterial agent also contains 1-2wt% K2O, which accounts for 1-2wt% of the surface thickness of the glass antibacterial agent with a surface thickness of 0-50nm.
[0037] Furthermore, the silver-loaded glass antibacterial agent exhibits an inhibition rate of over 99.99% against Staphylococcus aureus and Escherichia coli.
[0038] This solution also provides a method for preparing the silver-loaded glass antibacterial agent, as follows: Step 1: After preparing the raw materials, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃; Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours. Step 5: Wash the glass powder obtained in step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:(2-5). The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the finished product can be obtained.
[0039] Furthermore, the raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
[0040] Further, the nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is not less than 18 wt%, and the proportion of silver nitrate in the total nitrate can be 18 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 98 wt%, 99 wt%, or any range or subrange between two values. The second nitrate in step 5 is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is 0.15-0.35 wt%, and the proportion of potassium nitrate in the total second nitrate is not less than 70 wt%. Preferably, the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:(0.6-1), and the molar ratio of sodium content in the raw material to silver content in nitrate during the first ion exchange is 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1.
[0041] The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:(5-7), which can be 1:5, 1:6, or 1:7.
[0042] Example 1 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 9wt% Al2O3, 12wt% B2O3, 8wt% ZnO, 5wt% CaO, 12wt% Na2O, 0.5wt% K2O, 50wt% P2O5, 3wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.4µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:5. The composition of the nitrate is NaNO3:KNO3:AgNO3 = 78.31wt%:2.11wt%:19.58wt%. Perform ion exchange at 470℃ for 1 hour, followed by washing and drying to obtain the desired silver-loaded glass antibacterial agent. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 19.58wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during ion exchange is 1:0.6.
[0043] The prepared silver-loaded glass antibacterial agent was mixed with resin to make products. The antibacterial ability and anti-yellowing ability of resin products with different addition amounts of 0.15-1wt% were studied. When the proportion of silver-loaded glass antibacterial agent in the resin product was 1wt%, the antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively.
[0044] Example 2
[0045] Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 7wt% Al2O3, 11.4wt% B2O3, 10wt% ZnO, 4wt% CaO, 11.8wt% Na2O, 0.4wt% K2O, 52wt% P2O5, 3wt% SiO2 and 0.4wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.5µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:9, and perform ion exchange at 440℃ for 2 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 21.36 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:0.86.
[0046] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:2 and the ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 21.78wt%: 78.01wt%: 0.21wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:6.55.
[0047] SEM images of the prepared silver-loaded glass antibacterial agent are shown below. Figure 1 As shown, the prepared silver-loaded glass antibacterial agent was mixed with resin to make a product. The antibacterial ability and anti-yellowing ability of the resin products with different addition amounts of 0.15-1wt% were studied. When the proportion of silver-loaded glass antibacterial agent in the resin product was 0.5wt%, the antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively.
[0048] The overall silver content of the silver-loaded glass antibacterial agent was tested according to "GB / T 11066.11-2021 Gold Chemical Analysis Methods Part 11: Determination of the Content of Magnesium, Chromium, Manganese, Iron, Nickel, Copper, Palladium, Silver, Tin, Antimony, Lead and Bismuth by Inductively Coupled Plasma Mass Spectrometry". The silver content of the surface 0-50nm was tested according to "GB / T 24575-2009 Secondary Ion Mass Spectrometry Detection Method for Na, Al, K and Fe on Silicon and Epitaxial Wafer Surfaces".
[0049] Figure 5 This is a graph showing the test results of silver oxide, sodium oxide, and potassium oxide on the surface of the glass powder obtained in step 3 of this embodiment. Figure 6 This image shows the test results of silver oxide, potassium oxide, and sodium oxide on the surface of the final silver-loaded glass antibacterial agent obtained in this embodiment. Figure 5 and Figure 6 It can be seen that before ion exchange, the sodium oxide content on the surface of the glass powder is the highest, and it does not contain silver oxide. After ion exchange, the sodium oxide content decreases, while the contents of silver oxide and potassium oxide both increase, proving that silver enters the surface of the glass powder, thus playing an antibacterial role. Furthermore, from... Figure 6 As can be seen, the silver oxide content drops sharply after the surface thickness of the glass antibacterial agent exceeds 50 nm, proving that this application has successfully developed a glass antibacterial agent containing silver oxide that accumulates on the surface of glass powder.
[0050] Example 3
[0051] Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 11.6wt% B2O3, 11.2wt% ZnO, 3.5wt% CaO, 11.9wt% Na2O, 0.5wt% K2O, 53wt% P2O5, 2.8wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.2µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, and perform ion exchange at 450℃ for 3 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 24.48 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:0.76.
[0052] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3. The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the final product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 19.04wt%: 80.72wt%: 0.24wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:5.57.
[0053] The prepared silver-loaded glass antibacterial agent was mixed with resin to make products. The antibacterial ability and anti-yellowing ability of resin products with different addition amounts of 0.15-1wt% were studied. The proportion of silver-loaded glass antibacterial agent in the resin product was 0.5wt%. The antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively.
[0054] Example 4 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 3wt% Al2O3, 11.5wt% B2O3, 13wt% ZnO, 4.5wt% CaO, 12wt% Na2O, 0.5wt% K2O, 52wt% P2O5, 3wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.8µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:17, and perform ion exchange at 380-480℃ for 1-4 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 27.5 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:0.87.
[0055] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:4. The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the final product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 15.42wt%: 84.28wt%: 0.29wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:5.13.
[0056] The prepared silver-loaded glass antibacterial agent was mixed with resin to make products. The antibacterial ability and anti-yellowing ability of resin products with different addition amounts of 0.15-1wt% were studied. The proportion of silver-loaded glass antibacterial agent in the resin product was 0.5wt%. The antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively.
[0057] Example 5
[0058] Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 1.3wt% Al2O3, 11.5wt% B2O3, 15wt% ZnO, 4wt% CaO, 11.7wt% Na2O, 0.4wt% K2O, 53wt% P2O5, 2.6wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 4.1µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, and perform ion exchange at 380-480℃ for 1-4 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 30.41 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:1.
[0059] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:5. The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the final product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 7.5wt%: 92.16wt%: 0.34wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:5.06.
[0060] The prepared silver-loaded glass antibacterial agent was mixed with resin to make products. The antibacterial ability and anti-yellowing ability of resin products with different addition amounts of 0.15-1wt% were studied. When the proportion of silver-loaded glass antibacterial agent in the resin product was 0.5wt%, the antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively.
[0061] Comparative Example 1 Prepare the antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 4wt% AgO2, 12wt% B2O3, 8wt% ZnO, 5wt% CaO, 12wt% Na2O, 0.5wt% K2O, 50wt% P2O5, 3wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.6µm.
[0062] SEM images of the prepared silver-loaded glass antibacterial agent are shown below. Figure 3As shown, the prepared silver-impregnated glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-impregnated glass antibacterial agent in the resin product was 1 wt%. The antibacterial efficacy of this product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively. A yellowing test was performed on the product. Figure 4 As shown, when the amount added to PS resin is 1wt%, yellowing occurs after 150 hours under the test conditions.
[0063] Comparative Example 2 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 10wt% B2O3, 30wt% ZnO, 4.5wt% CaO, 2wt% Na2O, 50wt% P2O5, 3wt% AgO and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, perform ion exchange at 450℃ for 3 hours, then wash and dry to obtain the desired silver-loaded glass antibacterial agent. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for 24.68 wt% of the total nitrate. Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3 and the ion exchange is carried out at 360-460℃ for 1-4 hours. After washing with water and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 7.5wt%: 92.16wt%: 0.34wt%.
[0064] The prepared silver-impregnated glass antibacterial agent was mixed with resin to make a product. When the proportion of the silver-impregnated glass antibacterial agent in the resin product was 0.5 wt%, the antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively. A yellowing test was conducted on the product; when the amount added to ABS resin was 1 wt%, yellowing occurred after 200 hours under the test conditions.
[0065] Comparative Example 3 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 10wt% B2O3, 27wt% ZnO, 4.5wt% CaO, 50wt% P2O5, 3wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm and an average particle size of 1.5µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, perform ion exchange at 450℃ for 3 hours, then wash and dry to obtain the desired silver-loaded glass antibacterial agent. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for 25.36 wt% of the total nitrate. Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3 and the ion exchange is carried out at 360-460℃ for 1-4 hours. After washing with water and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 7.5wt%: 92.16wt%: 0.34wt%.
[0066] The prepared silver-loaded glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-loaded glass antibacterial agent in the resin product was 0.15 wt%. The antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 40% and 39.8%, respectively.
[0067] Comparative Example 4 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 10wt% B2O3, 14.5wt% ZnO, 5.5wt% CaO, 11wt% K2O, 0.5wt% Na2O, 50wt% P2O5, 3wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, perform ion exchange at 450℃ for 3 hours, then wash and dry to obtain the desired silver-loaded glass antibacterial agent. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for 28.26 wt% of the total nitrate. Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3 and the ion exchange is carried out at 360-460℃ for 1-4 hours. After washing with water and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 7.5wt%: 92.16wt%: 0.34wt%.
[0068] The prepared silver-impregnated glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-impregnated glass antibacterial agent in the resin product was 0.5 wt%. The antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 80% and 75.9%, respectively.
[0069] Comparative Example 5 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 1.3wt% Al2O3, 11.5wt% B2O3, 15wt% ZnO, 4wt% CaO, 11wt% Na2O, 0.4wt% K2O, 53wt% P2O5, 2.6wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:15, perform ion exchange at 500℃ for 5 hours, then wash and dry to obtain the desired silver-loaded glass antibacterial agent. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, wherein silver nitrate accounts for 28 wt% of the total nitrate. Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:(2-5) and the ion exchange is carried out at 480℃ for 5 hours. After washing with water and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3:AgNO3 = 7.5wt%:92.16wt%:0.34wt%.
[0070] The prepared silver-impregnated glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-impregnated glass antibacterial agent in the resin product was 0.5 wt%. The antibacterial effect of this product against Staphylococcus aureus and Escherichia coli was 99.9% and 99.99%, respectively. However, when the proportion of the antibacterial agent in the resin product was 1 wt%, the anti-yellowing ability also decreased, and yellowing occurred after 250 hours.
[0071] Comparative Example 6 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 11.6wt% B2O3, 11.2wt% ZnO, 3.5wt% CaO, 11.9wt% Na2O, 0.5wt% K2O, 53wt% P2O5, 2.8wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.2µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:10, and perform ion exchange at 450℃ for 3 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 16 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:0.52.
[0072] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3. The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the final product is obtained. The specific composition of the second nitrate is: NaNO3:KNO3:AgNO3 = 19.04wt%:80.72wt%:0.24wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:8.27.
[0073] The prepared silver-loaded glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-loaded glass antibacterial agent in the resin product was 0.5 wt%. The antibacterial effect of the product against Staphylococcus aureus and Escherichia coli was 85.4% and 85.2%, respectively.
[0074] Comparative Example 7 Prepare the silver-loaded antibacterial glass agent according to the following steps: Step 1: Prepare the following raw materials: 5wt% Al2O3, 11.6wt% B2O3, 11.2wt% ZnO, 3.5wt% CaO, 11.9wt% Na2O, 0.5wt% K2O, 53wt% P2O5, 2.8wt% SiO2 and 0.5wt% CeO2. Mix them using a V-type mixer at a speed of 5-10 rpm for 10-30 minutes. Then place the mixture in a platinum crucible and melt it at 1200-1500℃ for 2-8 hours. Step 2: The molten liquid obtained in Step 1 is formed into sheets using a roller forming machine or directly subjected to water quenching; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm, and the average particle size of the powder is 3.2µm. Step 4: Mix the glass powder obtained in Step 3 with nitrate at a mass ratio of 1:20, and perform ion exchange at 450℃ for 3 hours. After washing and drying, the desired silver-loaded glass antibacterial agent is obtained. The nitrate is a mixture of sodium nitrate, potassium nitrate, and silver nitrate, with silver nitrate accounting for 24.48 wt% of the total nitrate. The molar ratio of sodium content in the raw material to silver content in the nitrate during the first ion exchange is 1:0.76.
[0075] Step 5: Wash the glass powder obtained in Step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:3. The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the finished product is obtained. The specific composition of the second nitrate is: NaNO3: KNO3: AgNO3 = 45.57wt%: 54.25wt%: 0.18wt%. The molar ratio of silver content in the nitrate during the first ion exchange to potassium content in the second nitrate is 1:3.86.
[0076] The prepared silver-impregnated glass antibacterial agent was mixed with resin to make a product. The proportion of the silver-impregnated glass antibacterial agent in the resin product was 1 wt%. The antibacterial efficacy of this product against Staphylococcus aureus and Escherichia coli was 99.99% and 99.9999%, respectively. During the yellowing test, it was found that the product yellowed after 150 hours.
[0077] The antibacterial properties of the products from Examples 1-5 and Comparative Examples 1-7 were tested using the ASTM E2149-13a shaking flask method. The yellowing properties of the products from Examples 1-5 and Comparative Examples 1-5 were also tested under the following conditions: continuous ultraviolet irradiation (wavelength 300-700nm, 255W / m²) using an ultraviolet irradiation device (CME-SEB500 device manufactured by Zhongwei Keneng (Beijing) Technology Co., Ltd.). 2 The yellowing phenomenon after irradiation was observed. The results of the antibacterial and yellowing performance tests are shown in Table 1 and Table 2, respectively.
[0078] Table 1. Test results of antibacterial properties of the products from Examples 1-5 and Comparative Examples 1-5. sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Average radius of antibacterial agent (µm) 3.4 3.5 3.2 3.8 4.1 3.6 3.4 3.6 3.7 4.2 Silver content (wt%) in the 0-50nm range of the surface 7.8 7.2 6.7 6.3 5.5 6.2 5.3 1.5 1.2 3.6 Resin type Polystyrene (PS) Acrylonitrile-butadiene-styrene copolymer (ABS) Polypropylene (PP) Polycarbonate (PC) Polyethylene (PE) Polystyrene (PS) Acrylonitrile-butadiene-styrene copolymer (ABS) Polypropylene (PP) Polycarbonate (PC) Polyethylene (PE) Percentage (wt%) in resin products 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Antibacterial activity of Staphylococcus aureus 99.99 99.99 99.99 99.99 99.99 99.99 99.99 40 67.2 96.2 antibacterial activity of Escherichia coli 99.9999 99.9999 99.9999 99.9999 99.9999 99.9999 99.9999 39.8 74.3 98.5 Table 2. Yellowing test results of products from Examples 1-5 and Comparative Examples 1-5 sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Resin type Polystyrene (PS) Acrylonitrile-butadiene-styrene copolymer (ABS) Polypropylene (PP) Polycarbonate (PC) Polyethylene (PE) Polystyrene (PS) Acrylonitrile-butadiene-styrene copolymer (ABS) Polypropylene (PP) Polycarbonate (PC) Polyethylene (PE) percentage of resin products 1 1 1 1 1 1 1 1 1 1 After 100 hours of irradiation OK OK OK OK OK OK Okay Okay Okay Okay After 150 hours of irradiation OK OK OK OK OK Yellowing Okay Okay Okay Okay After 200 hours of irradiation Yellowing OK OK OK OK Yellowing Yellowing Okay Okay Okay After 250 hours of irradiation Yellowing OK OK OK OK Yellowing Yellowing Yellowing Yellowing Yellowing Meanwhile, the applicant also studied and compared the addition of different amounts of antibacterial agent in resin, specifically including the addition of 0.5 wt% and 1 wt% antibacterial agent. The results showed that the glass antibacterial agent added in Examples 1-5 of this invention, within the range of 0.15-1 wt%, exhibited excellent antibacterial performance against Staphylococcus aureus and Escherichia coli, and remained unchanged in color for 250 hours. In contrast, the comparative examples generally required an addition amount of more than 0.5 wt% to achieve a good antibacterial effect, but yellowing usually occurred after 200 hours or even 150 hours, making it difficult to achieve both antibacterial properties and tissue yellowing simultaneously.
Claims
1. A silver-impregnated glass antibacterial agent, characterized in that, The silver oxide in this silver-plated glass antibacterial agent accounts for 5-8 wt% of the surface thickness of the silver-plated glass antibacterial agent (0-50 nm) and [r]% of the total silver-plated glass antibacterial agent. 3 -(r-0.05) 3 ] / r 3 ×W, where r is the radius of the silver-loaded glass antibacterial agent, and W is the mass percentage of silver oxide content in the silver-loaded glass antibacterial agent with a surface thickness of 0-50nm.
2. The silver-loaded glass antibacterial agent according to claim 1, characterized in that, The silver-loaded glass antibacterial agent has an inhibition rate of over 99.99% against Staphylococcus aureus and Escherichia coli.
3. The silver-loaded glass antibacterial agent according to claim 1 or 2, characterized in that, The potassium oxide in the silver-loaded glass antibacterial agent accounts for 1-2 wt% of the glass antibacterial agent with a surface thickness of 0-50 nm.
4. A method for preparing the silver-loaded glass antibacterial agent as described in claim 1, characterized in that, Includes the following steps: Step 1: After preparing the raw materials according to the specified ratio, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃. Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours.
5. The method for preparing silver-loaded glass antibacterial agent according to claim 4, characterized in that, The raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
6. The method for preparing silver-loaded glass antibacterial agent according to claim 4, characterized in that, The nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is not less than 18 wt%.
7. A method for preparing the silver-loaded glass antibacterial agent as described in claim 3, characterized in that, Includes the following steps: Step 1: After preparing the raw materials according to the specified ratio, mix them and then place them in a crucible to melt the raw materials at 1200-1500℃. Step 2: Shape the melt obtained in Step 1 into sheets or directly quench it in water; Step 3: Grind the glass obtained in Step 2 into glass powder with a D50 of less than 10µm; Step 4: Mix the glass powder obtained in step 3 with nitrate at a mass ratio of 1:(5-20) and carry out ion exchange at 380-480℃ for 1-4 hours. Step 5: Wash the glass powder obtained in step 4 with water to remove nitrates, then dry it. After drying, perform a second ion exchange. During the second ion exchange, the glass powder and the second nitrate are mixed at a mass ratio of 1:(2-5). The ion exchange is carried out at 360-460℃ for 1-4 hours. After washing and drying, the finished product can be obtained.
8. The method for preparing silver-loaded glass antibacterial agent according to claim 7, characterized in that, The raw materials in step 1 consist of: 1-10 wt% Al2O3, 11-12 wt% B2O3, 8-15 wt% ZnO, 3-5 wt% CaO, 11-12 wt% Na2O, 0.1-0.5 wt% K2O, 50-55 wt% P2O5, 2-3 wt% SiO2, and 0.2-0.5 wt% CeO2.
9. The method for preparing silver-loaded glass antibacterial agent according to claim 7, characterized in that, The nitrate in step 4 is a mixture of sodium nitrate, potassium nitrate and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is not less than 18 wt%; the second nitrate in step 5 is a mixture of sodium nitrate, potassium nitrate and silver nitrate, wherein the proportion of silver nitrate in the total nitrate is 0.15-0.35 wt% and the proportion of potassium nitrate in the total second nitrate is not less than 70 wt%.
10. A silver-impregnated glass antibacterial agent product, characterized in that, It is composed of resin and the silver-loaded glass antibacterial agent as described in claim 1 or claim 3, wherein the silver-loaded glass antibacterial agent accounts for 0.15-1 wt% of the product.